2013
DOI: 10.1517/17530059.2013.808621
|View full text |Cite
|
Sign up to set email alerts
|

Molecular biomarkers in cervical cancer diagnosis: a critical appraisal

Abstract: The most promising cytological biomarkers for cervical cancer screening are p16(INK4a)/Ki-67 dual immunostaining, methylation of CADM1 and MAL and viral integration. Although some of the biomarkers are very promising for this purpose, no studies have evaluated how accurately these biomarkers classify or predict the outcome. Additional clinical trials are needed to determine the true clinical value of these promising cytological biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 92 publications
1
41
0
1
Order By: Relevance
“…Dozens of methylated genes have been discovered to aid the screening and diagnosis of cervical cancer . Among them, CADM1 , MAL , and PCDH10 have been established as tumor suppressor genes, and their methylation are highly related to the severity of cervical noeplasia .…”
Section: Discussionmentioning
confidence: 99%
“…Dozens of methylated genes have been discovered to aid the screening and diagnosis of cervical cancer . Among them, CADM1 , MAL , and PCDH10 have been established as tumor suppressor genes, and their methylation are highly related to the severity of cervical noeplasia .…”
Section: Discussionmentioning
confidence: 99%
“…Distinguishing low‐grade from high‐grade dysplasia in genital lesions has particular importance for patient management and treatment, which may range from ‘watchful waiting’ to the use of topical therapy, cryotherapy, laser treatments and/or surgical excision. Positive p16 immunostaining has been used as a biomarker of high‐grade dysplasia and malignancy, particularly in cervical specimens . In non‐mucosal skin, p16 immunostaining is able to discriminate typical cases of condyloma acuminatum (CA) from bowenoid papulosis (BP), with perfect concordance to hematoxylin and eosin (H&E) findings …”
mentioning
confidence: 99%
“…Other cross-sectional studies in CIN have revealed patterns of aberrant DNA methylation in specific genes, including for tumor suppressor genes CDKN2A [34–37], MGMT [19, 38], HIC1, APC, CADM1, MAL , and RARβ [6, 9, 12]. However, as these prior studies were cross-sectional, the predictive nature and timing of the gene methylation has not yet been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the cross-sectional design of prior studies, it remains unclear whether the identified epigenetic changes preceded or followed the disease. Also, prior studies focused primarily on gene promoter regions where DNA methylation would be expected to silence genes, whereas the broad profile of aberrant DNA methylation events within genes associated with cervical tumorigenesis remains unknown [6, 12]. This is a major limitation, since differential methylation of intragenic sites (i.e., within exonic and intronic regions) have been associated with differential, and often increased, expression of tumor suppressor genes predictive of clinical progression in cervical cancer [13, 14].…”
Section: Introductionmentioning
confidence: 99%